Learning environment as a human-centered system for optimizing gifted and talented childhood potential - Anelfa Eka Maulina; Syafrimen; Aisyah Hana Robbani (CV. SPDFHarmony, 2025)
Background: Gifted and talented children possess exceptional intellectual and creative potential that requires appropriate environmental support to be optimally developed. Beyond innate ability, the learning environment plays a decisive role in mediating interactions between children’s characteristics, instructional practices, and learning experiences. However, studies that conceptualize the learning environment as a human-centered system supporting gifted childhood development remain limited, particularly within early childhood education contexts. Aims: This study aims to examine how learning environments function as human-centered systems in optimizing the potential of gifted and talented children, with emphasis on physical, psychological, and social environmental dimensions. Method: This study employed a Systematic Literature Review approach guided by PRISMA procedures. A total of 23 international journal articles and one academic book indexed in Scopus, ScienceDirect, and Google Scholar were analyzed using thematic synthesis. The analysis focused on identifying key environmental dimensions, human factors, and their roles in supporting gifted childhood development. Results: The findings reveal three interrelated dimensions of learning environments that support gifted potential: physical environments that provide adequate resources and learning spaces, psychological environments that foster motivation and emotional security, and social environments characterized by competent teachers and supportive relationships. These dimensions interact dynamically to facilitate academic excellence, creativity, and socio-emotional development in gifted children. Conclusion: The learning environment functions as a human-centered system that mediates the development of gifted and talented children. Optimizing gifted potential requires the integration of physical, psychological, and social environmental supports within early childhood education.